Cost-effectiveness analysis of sodium zirconium cyclosilicate for treating hyperkalemia among Chinese patients - Tian, Lei; Fu, Shihui; Li, Mengyuan; Zhao, Xinrui; Li, Hongchao (Frontiers in Public Health, 2023)
Objectives: Hyperkalemia most commonly develops in chronic kidney disease (CKD) or heart failure (HF) patients. Sodium zirconium cyclosilicate (SZC) is a new selective potassium (K+) binder for treating hyperkalemia. The aim of this study was to evaluate the cost-effectiveness of SZC versus usual care for the treatment of hyperkalemia among CKD patients or HF patients in China. Methods: Individual patient microsimulation models were constructed to simulate a CKD cohort until the initiation of renal replacement therapy (RRT) and a HF cohort across the lifetime horizon. K+ levels were based on two phase 3 clinical trials. Health state utility and event incidence rates were retrieved from literature. Drug costs and healthcare utilization costs were obtained from negotiated price, literature, and expert interviews. Costs and quality-adjusted life-years (QALYs) were both discounted at 5%. The main outcomes were overall costs, QALYs, and incremental cost-effectiveness ratio (ICER). The willingness-to-pay (WTP) threshold in China is CNY 80,976-242,928/QALY, which is one to three times the gross domestic product per capita. Sensitivity analyses were performed to characterize the models’ uncertainty. Results: In the HF cohort, the base case results revealed that SZC was associated with 2.86 QALYs and the total cost was CNY 92,671.58; usual care was associated with 1.81 QALYs and CNY 54,101.26. In the CKD cohort, SZC was associated with 3.23 QALYs and CNY 121,416.82 total cost; usual care was associated with 2.91 QALYs and CNY 111,464.57. SZC resulted in an ICER of CNY 36,735.87/QALY for the HF cohort and CNY 31,181.55/QALY for the CKD cohort, respectively. The one-way and probability sensitivity analyses found that the results were robust. Conclusion: SZC is a cost-effective treatment compared to usual care in HF and CKD patients. SZC is an important novel treatment option for managing patients with hyperkalemia in China.